METODE BERCERITA UNTUK MENGATASI KETERLAMBATAN BAHASA ANAK USIA DINI - Widayawan, Aqillah Nuhaa; Budiman, Meia Agatha; Fidrayani, Fidrayani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
This study aims to address language development delays in early childhood through the storytelling method. The background of this study is based on the importance of language development in children's lives, which affects their social and academic abilities. The subjects of this research were 4-5 years old children at RA Generasi Qur'ani Ujung Bandar. The research was conducted using a literature study approach from various scientific references. Data shows that around 5-10% of early childhood experience language delays, caused by internal factors such as health and external factors such as the environment. The results revealed that the storytelling method was able to improve children's speaking and listening skills, with significant improvements in vocabulary and narrative ability. This approach also stimulates creativity and increases children's confidence in communicating.